PENGEMBANGAN MEDIA PEMBELAJARAN POSTER FISIKA FLUIDA STATIS BERBASIS LINGKUNGKAN DALAM BENTUK POSTER PHOTOSCRAP - Fierda Zahara Jannah; Vina Serevina; Made Astra (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
The aim of this research is to produce the learning media in the form photoscrap as media on the subject of statis fluid for students 10 grade in senior high school. Poster developed in this research created from recycled material or scrap. The method which used in this research is a research and development (R&D) methods of Dick and Carey with steps : 1) identification instructional needs and writing general instructional purposes , 2) instructional analysis, 3) identification first behavior characteristic of students, 4) writing spesific instructional purposes, 5) design assesment tools, 6) desain instructional strategy, 7) development instructional materials , 8) desain and emplement formative evaluation, 9) instructional sysetem, 10 ) implementation summatif evaluation and innovasion difusion. Instrument of research in the form of questionnaire. This poster has been through a validation test phase with a percentage 81,25% according to matter expert, 79.95% according to media expert, and 94.85% according to physics teacher in senior high school interpreted very good. Limited test result on physics learners shows the percentage 85.54% from 5 aspect assessment of students to poster developed. Based on the result of the validation test, experiment, it can be concluded that the result of the development of fluid poster in form of photoscrap has been qualified as a media of learning for the ten grades in senior high school in their physics class. Keywords : Instructional media, poster, photoscrap, static fluid